Investigating gender as a moderator of extreme-context perception effects on behavioural tendencies towards fashion brands on Instagram in West Africa - Mahmoud, Ali B.; Berman, Alexander; Grigoriou, Nicholas; Solakis, Konstantinos (My University, 2023)
This study draws on the Gender Schema Theory, Technology Acceptance Model (TAM), Uses and Gratifications Theory (U&G), and Social Cognitive Theory (SCT) to explore how gender moderates the relationship between extreme-context perception and user intentions on Instagram for fashion brands, drawing on the COVID-19 pandemic as an example of extreme context. Specifically, our study context concerns social media users in West Africa during the COVID-19 pandemic in 2021. Through a time-lagged online survey, the data of 310 Instagram users based in Uganda and Nigeria were obtained and subsequently analysed using a variance-based structural equation modelling. Our analysis supports previously reported results in the literature by demonstrating the positive effects of extreme-context perception on intentions to follow and recommend fashion brands on Instagram. Furthermore, our results present new evidence that gender moderates extreme-context perception effects, such that men are significantly more likely to develop higher usefulness, enjoyment, satisfaction and intentions to recommend and follow fashion brands on Instagram. This empirical investigation expands our knowledge of social media use by demonstrating the moderating role of gender regarding the way extreme-context perception affects consumer behaviour towards fashion brands on social media.
Keywords: Gender; COVID-19; Perception; Pandemic; Extreme context; Social media marketing